2016
DOI: 10.1016/j.forpol.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use and land use changes on the resilience of beekeeping in Uruguay

Abstract: We use a social-ecological systems framework and interview data from key informants to analyze the threshold dynamics underpinning the resilience of the local beekeeping sector, amidst changes in land use (management) and land use changes (conversions) that result from the expansions of the soy and eucalypt frontiers in Uruguay.Our results indicate that while agriculture began displacing grasslands that originally provided high yields of honey, afforestation now compensates those losses through the flowerings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…These results are of interest when comparing them with earlier research on international pulp investments in Chile and Uruguay, in which Ehrnström-Fuentes and Kröger (2017) found that corporate-community relations tend to be dynamic and contentious, and certain stakeholder voices tend to become marginalized. To reach a wide-level social license to operate, it is clearly important to understand how local people engage with their various livelihood alternatives in communities impacted by large-scale pulp investments (see also Malkamäki et al 2016 on the related case of Uruguay). In BR4, for example, the interviewed manager pointed out that "the company is still creating tools to deal with its social issues, because they are different from environmental ones.…”
Section: Perspectives On the Role Of Iso 26000 Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are of interest when comparing them with earlier research on international pulp investments in Chile and Uruguay, in which Ehrnström-Fuentes and Kröger (2017) found that corporate-community relations tend to be dynamic and contentious, and certain stakeholder voices tend to become marginalized. To reach a wide-level social license to operate, it is clearly important to understand how local people engage with their various livelihood alternatives in communities impacted by large-scale pulp investments (see also Malkamäki et al 2016 on the related case of Uruguay). In BR4, for example, the interviewed manager pointed out that "the company is still creating tools to deal with its social issues, because they are different from environmental ones.…”
Section: Perspectives On the Role Of Iso 26000 Standardmentioning
confidence: 99%
“…A structural change is occurring in the forest products trade and investment sector due to saturation of the traditional main markets in North America and Europe, while the emerging economies of Brazil, India, and China have opened up with much higher demand growth prospects (Hetemäki et al 2016). The internationalization of large-scale forest industry firms has led to the expansion of plantation area and pulp production in the global south, which has raised concerns regarding the threat of forest resource overuse and inherent sustainability challenges (Malkamäki et al 2016, Toppinen et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, mass-flowering crops, like eucalyptus, can reduce pollination services to other crops and act as a pollinator "sink" during peak bloom periods potentially lowering pollination rates and harvests for adjacent pollinator-dependent crops (Holzchuh et al 2011). In nearby Uruguay, E. grandis is being replaced by another faster-growing eucalyptus species that does not flower before it is harvested, and beekeepers there are concerned about the loss of the floral resources for their bees (Malkamäki et al 2016). Future research should also directly consider the value of eucalyptus flowers as floral resources for wild bees, and consider the trade-offs with other land uses that provide more consistent and year-round flowering.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of afforested plantations on native bees and wasps is largely unknown; the majority of the research on plantations and bees has focused on honey bees (Malkamäki et al, 2016) or eucalyptus pest species like gall wasps (Aquino et al, 2011) with little information on plantations as habitats for pollinating bees . Understanding how wild bee populations respond to this type of LULC is critical because of the rapid expansion of tree plantations that now account for 277.9 million hectares worldwide, a full 7% of the Earth's forests (FAO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, if a grassland is dominated by grasses and lacking in flowering forbs, it will be of low value as a forage source for honey bees (Smith 1964, Palmer 2008. Native grasslands, including both native tropical grasslands such as savannas (Abdullahi et al 2011, Dukku 2013 and native temperate grassland such as steppe habitats extending across eastern Europe and central Asia (Kim 2018), pampas in South America (Malkamäki et al 2016) and prairies in North America may provide favorable choices as apiary locations. Conservation grasslands such as CRP (Conservation Reserve Program) areas in the U.S. containing native prairie plants have been shown to support honey bee colonies .…”
Section: Variation In Landscape Composition Affects Availability and mentioning
confidence: 99%